Safety and Efficacy of Laparoscopic Caudate Lobectomy: A Systematic Review - Panagiotis Dorovinis (MDPI AG, 2021)
Resection of the caudate lobe of the liver is considered a highly challenging type of liver resection due to the region’s intimacy with critical vascular structures and deep anatomic location inside the abdominal cavity. Laparoscopic resection of the caudate lobe is considered one of the most challenging laparoscopic liver procedures. The objective of our systematic review was to evaluate the safety, technical feasibility and main outcomes of laparoscopic caudate lobectomy LCL. A systematic review of the literature was undertaken for studies published until September 2021. A total of 20 studies comprising 221 patients were included. Of these subjects, 36% were women, whereas the vast majority of resections (66%) were performed for malignant tumors. Tumor size varied significantly between 2 and 160 mm in the largest diameter. The mean operative time was 210 min (range 60–740 min), and estimated blood loss was 173.6 mL (range 50–3600 mL). The median hospital length of stay LOS was 6.5 days (range 2–15 days). Seven cases of conversion to open were reported. The vast majority of patients (93.7%) underwent complete resection (R0) of their tumors. Thirty-six out of 221 patients developed postoperative complications, with 5.8% of all patients developing a major complication (Clavien–Dindo classification ≥ III).No perioperative deaths were reported by the included studies. LCL seems to be a safe and feasible alternative to open caudate lobectomy OCL in selected patients when undertaken in high-volume centers by experienced surgeons.